Polymyxin B and fusidic acid, a novel potent synergistic combination against Klebsiella pneumoniae and Escherichia coli isolates with polymyxin B resistance - Chen, Shuying; Zhou, Peiyao; Wu, Chunyang; Wang, Jie; Zhou, Ying; Zhang, Jiao; Wang, Bingjie; Zhao, Huilin; Rao, Lulin; Li, Meilan; Yu, Fangyou; Lin, Chunchan (Frontiers in Microbiology, 2023)
The increasing prevalence of multidrug-resistant (MDR) Gram-negative bacteria and comparatively limited options of antibiotics pose a major threat to public health worldwide. Polymyxin B is the last resort against extensively resistant Gram-negative bacterial infections. However, a large number of Gram-negative bacteria exhibited high-level resistance to Polymyxin B, bringing challenges for antimicrobial chemotherapy. Combination therapies using polymyxins and other antibiotics are recommended to treat multidrug-resistant pathogens.In this study, we selected Gram-negative bacterial strains, including Klebsiella pneumoniae and Escherichia coli, to explore whether fusidic acid and polymyxin B have a synergistic killing effect. Through broth microdilution, we observed that minimum inhibitory concentrations (MICs) against polymyxin B in the isolates tested were significantly reduced by the addition of fusidic acid. Notably, chequerboard analysis indicated a synergistic effect between polymyxin B and fusidic acid. In addition, subsequent time-kill experiments showed that the combination of polymyxin B and fusidic acid was more effective than a single drug in killing bacteria. Finally, our investigation utilizing the murine model revealed a higher survival rate in the combination therapy group compared to the monotherapy group.Our research findings provide evidence of the synergistic effect between polymyxin B and fusidic acid. Fusidic acid was shown to increase the sensitivity of multi-drug resistant E. coli and K. pneumoniae to polymyxin B, thereby enhancing its bactericidal activity. This study provides new insights into a potential strategy for overcoming polymyxin B resistance, however, further investigations are required to evaluate their feasibility in real clinical settings.